Cognitive MIMO radio: an emerging paradigm for enhancing wireless access capability. (6th January 2009) - Baccarelli, Enzo; Biagi, Mauro; Pelizzoni, Cristian; Cordeschi, Nicola
In this contribution, we explore the access performance of cognitive multiple-input multiple-output (MIMO) radio, a novel paradigm that should combine the flexibility features of cognitive radio with the multiplexing capabilities of the multi-antenna one. As application scenario, we consider the (Rayleigh flat-faded) uplink of a WLAN working in infrastructure-mode, where non-cooperative multi-antenna cognitive radios attempt to join to a (possibly multi-antenna) access point (AP). The target of each radio is the competitive maximisation of own access throughput in the presence of (spatially-colored) multiple-access interference (MAI). Being the radios cognitive, they are capable to 'sense' the ambient-context and 'self-reconfigure' their access strategy via suitable power-allocation and spatial signal-shaping. Hence, by exploiting these cognitive capabilities, the access to the MIMO uplink is modelled as a non-cooperative strategic game. An iterative and scalable algorithm is developed that allows to play the resulting access game in a distributed and asynchronous way (under both best-effort and 'contracted-QoS' access policies) by resorting on the implementation of MAI-mitigation strategies.